2005
DOI: 10.1007/s00542-005-0064-0
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear study of the hemispherical rotor bushing in a variable capacitance micromotor

Abstract: Friction and wear are the most serious problems for micromotors in microelectromechanical systems (MEMS). In the paper, a linear-sliding wear model of the contact between the rotor bushing and the ground plane is presented to describe the wear and a corresponding simplified method is proposed to simulate the wearing process. The effects of geometry parameters, material properties and applied operating conditions on the evolution of dimensional and volumetric wear rates and frictional torques are explored for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Alteration of the adhesion, friction, and electrical characteristics by micro-/nanoscale wear processes could be detrimental to the device functionality and efficiency. Despite significant progress in fabrication processes and design of agile MEMS devices [2], the operation lifetime of such microsystems is still limited by excessive adhesion forces, high wear rates, and rapid evolution of contact fatigue [6], [7]. Cessation of the microdevice operation due to surface degradation and lack of insight into the underlying failure mechanisms are major obstacles, limiting the application range of MEMS.…”
Section: Icroelectromechanical Systems (Mems)mentioning
confidence: 99%
See 1 more Smart Citation
“…Alteration of the adhesion, friction, and electrical characteristics by micro-/nanoscale wear processes could be detrimental to the device functionality and efficiency. Despite significant progress in fabrication processes and design of agile MEMS devices [2], the operation lifetime of such microsystems is still limited by excessive adhesion forces, high wear rates, and rapid evolution of contact fatigue [6], [7]. Cessation of the microdevice operation due to surface degradation and lack of insight into the underlying failure mechanisms are major obstacles, limiting the application range of MEMS.…”
Section: Icroelectromechanical Systems (Mems)mentioning
confidence: 99%
“…Many of these microdevices (e.g., micromotors [2], microswitches [3], and digital micromirrors [4]) contain components with load-bearing contact interfaces. As a result of the large surface-to-volume ratio of the microstructures comprising these systems, failure is controlled by micro-/nanoscale surface damage (wear) processes [5], [6].…”
Section: Icroelectromechanical Systems (Mems)mentioning
confidence: 99%
“…In the former studies of our group, the contact between the rotor and the bearing hub in a typical electrostatically actuated micromotor was studied and the sliding wear between the rotor bushing and ground plane was numerically simulated [7,8]. The results showed that the contact and non-linear effects cannot be ignored at microscale.…”
Section: Introductionmentioning
confidence: 98%
“…Accordingly, surface phenomena such as stiction, friction, and wear significantly affect the behavior of microsystems due to the high surface area-to-volume ratio [3][4][5]. Stiction, friction, and wear limits the application capabilities of MEMS devices with moving parts.…”
Section: Introductionmentioning
confidence: 99%
“…The contact area may be reduced by texturing the surface or by using microstructures such as bushings [22][23][24][25][26][27][28]. Bushings with various shapes are normally used as supporting structures in micromotors or microgears.…”
Section: Introductionmentioning
confidence: 99%